Time Use During the Great Recession - Aguiar, Mark; Hurst, Erik; Karabarbounis, Loukas (American Economic Review, 2013)
Using data from the American Time Use Survey between 2003 and 2010, we document that home production absorbs roughly 30 percent of foregone market work hours at business cycle frequencies. Leisure absorbs roughly 50 percent of foregone market work hours, with sleeping and television watching accounting for most of this increase. We document significant increases in time spent on shopping, child care, education, and health. Job search absorbs between 2 and 6 percent of foregone market work hours. We discuss the implications of our results for business cycle models with home production and non-separable preferences. (JEL D31, E32, J22)